Blue mussels’ valve behavior exhibits daily and lunar rhythms during the high Arctic polar day - Le Moal, Alexandre; Payton, Laura; Andrade, Hector; Camus, Lionel; Ballantine, Carl; Ciret, Pierre; Tran, Damien (Marine Biology, 2023)
International audience Marine species exhibit a multitude of biological rhythms, in accordance with their complex ecosystem governed by sun, earth and moon trajectories. Because of the inclination of the earth’s axis, the high Arctic ecosystem is characterized by several months of permanent illumination during the polar day. The persistence of biological rhythms in this photic context remains unclear. Yet, this information is crucial for the understanding of polar ecosystems functioning, as well as to predict the impact of future climate changes. Particularly, the impact of extreme photoperiods on recent invasive species remains largely unknown. Here, we investigate how environmental cycles shape the behavior of a re-emerging polar resident, the mussel Mytilus sp. during polar day (17 April to 26 August 2020; Svalbard, Ny-Ålesund, 78°56ʹ N, 11°56ʹ E). Our results show that in the high Arctic polar day, mussels’ behavior is shaped by both the photoperiod and the diel sun trajectories above the horizon. In addition, mussels also exhibit tidal, semi-lunar, and lunar rhythms of valve opening amplitude. We argue that these rhythms may have ecosystems functioning implications, and that the mussels’ ability to deal with drastic light regimes may explain their northward expansion and new resettlement in high Arctic.